Relationship Application Of Professional Nursing Practice Models With The Level Of Working Satisfaction Of Nurses In The MPKP Room Of Lasinrang Pinrang Hospital - Muslimin; Werna Nontji; Burhanuddin Bahar; Safruddin (Comprehensive Health Care, 2020)
Professional Nursing Practice Model (MPKP) is a method of comprehensive nursing care in providing quality nursing care. This study aims to investigate the correlation between the implementation of the professional nursing practice model and the work satisfaction rate of the working nurses at the MPKP room of the Regional Hospital of Lasinrang in Pinrang. The study is analytically observational with a cross-sectional design. The subject (n=124) are practicing nurses in the inpatient ward of Lasinrang Regional Hospital of Pinrang. The sample was selected employing a systematic random sampling technique. The data were obtained with a questionnaire distribution and observation checklist and the data were analyzed with univariate and bivariate measures. The chi-square test proves that the operand (p=0.000), pre-Competence (p=0.000), competence (p=0.000), competence case (p=0.164), and round (p=0.164) on the work satisfaction rate of the working nurses. This implies that there is a significant correlation the operand evaluation, pre-conference, post-conference, and the work satisfaction rate of the working nurses for the value of p<0.05 but no significant correlation between case competency evaluation as well as round and the work satisfaction of the nurses with p>0.05.